Improving access to research literature in developing countries : challenges and opportunities provided by Open Access - Chan, Leslie (2005)
The Open Access movement has grown from pockets of regional initiatives to an increasingly coordinated world wide movement, facilitated by common technical standards and open source software. While debates on open access have focused on the so-called “serial crisis” and copyright issues, relatively little attention has been paid to the myriads of benefits OA provide, particularly to researchers in the developing countries. In this paper, we highlight important developments and experimentations in knowledge sharing enabled by different modes of open access, and point to collaborative and sustainable models that will be highly beneficial to research institutions in the developing world in the long term. The recommendations in this2 paper will have important implications for library and information professionals working in resource poor countries.